Nuclear data for space exploration - Smith, Michael S.; Vogt, Ramona L.; LaBel, Kenneth A. (Frontiers in Astronomy and Space Sciences, 2023)
Understanding the harmful effects of galactic cosmic rays (GCRs) on space exploration requires a substantial amount of nuclear data. Specifically, the interaction of energetic GCR charged particles with spacecraft materials generates secondary radiations that, through energy deposition, can harm astronauts and electronic systems. By identifying the gaps in our knowledge of the relevant nuclear data -such as interaction cross sections -and identifying ways to fill those gaps -with measurements, compilations, evaluations, dissemination, reaction modeling, sensitivity studies, and uncertainty quantification -the safety and viability of space exploration can be improved. This work surveys the state of the art in this interdisciplinary field and identifies promising collaborative research topics that have significant potential to advance our understanding of the effects of the space radiation environment on space exploration.